-2(3a+1)=5(1-a)

Simple and best practice solution for -2(3a+1)=5(1-a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3a+1)=5(1-a) equation:



-2(3a+1)=5(1-a)
We move all terms to the left:
-2(3a+1)-(5(1-a))=0
We add all the numbers together, and all the variables
-2(3a+1)-(5(-1a+1))=0
We multiply parentheses
-6a-(5(-1a+1))-2=0
We calculate terms in parentheses: -(5(-1a+1)), so:
5(-1a+1)
We multiply parentheses
-5a+5
Back to the equation:
-(-5a+5)
We get rid of parentheses
-6a+5a-5-2=0
We add all the numbers together, and all the variables
-1a-7=0
We move all terms containing a to the left, all other terms to the right
-a=7
a=7/-1
a=-7

See similar equations:

| 8(1+x)=-22+2x | | X=0.3x5 | | 50=q/10+48 | | 11-x=35 | | 310=58+4x | | 3(x+1)=4(x+6) | | 2(2u-5)=u+2 | | 40+60x=460 | | 2(3x+1)=5(2x+3) | | 11x+14=2x+158 | | 96=4(b+6) | | 26x-125=x | | 7c-2=4c+13 | | 3j-22=-4-3j | | 4(m+4)^2−4m^2+20=276 | | -p+3p=-7+p | | -3x+17=-(17+3x) | | -6y=-4y-18 | | 6(b-10)=8(6+8) | | 4x+7=75-8 | | 2^(x)=32000 | | 3(1-4p)=30-3p | | 8n-6=250 | | 5(3m-8)=38+2m | | 8p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p | | 28=-5(u+1)-2 | | -5v-9(v+6)=-96 | | 21-2w=13 | | 16+6s+9s=16 | | 63=-9a+3(a+3) | | 5(5-2x)=115 | | -8=-v+12/3 |

Equations solver categories